Robotic Glove Therapy in Stroke Rehabilitation: A Scoping Review of Current Evidence and Research Trends - Eza Kemal Firdaus; Jony Francisco Dos Santos Silva; Devi Harmita (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
Stroke remains a leading cause of long-term disability worldwide, with persistent upper limb and hand impairments substantially restricting functional independence and quality of life. Robotic glove therapy has emerged as an innovative wearable rehabilitation technology designed to deliver high-intensity, repetitive, and task-specific hand training to stimulate neuroplastic recovery. Despite growing clinical interest, the breadth of current evidence and its translational implications remain insufficiently synthesized. This scoping review aimed to systematically map existing research on robotic glove therapy in stroke rehabilitation, identify methodological gaps, and analyze technological and clinical outcome trends. The review followed the PRISMA-ScR framework. A comprehensive search of PubMed, ScienceDirect, ProQuest, Google Scholar, and national index databases identified 110 records published between 2016 and 2026. After duplicate removal and eligibility screening, eight studies were included in the final synthesis, comprising randomized controlled trials, pilot trials, double-blind studies, and case reports conducted in Europe, Asia, and North America. The findings indicate that robotic glove interventions—including soft robotic gloves, EMG-driven systems, passive mobilization devices, and hand exoskeleton gloves consistently improved upper limb motor outcomes, hand dexterity, grip strength, spasticity, pain, and activities of daily living. Technologies incorporating intention-driven or EMG-triggered control demonstrated superior functional gains, underscoring the importance of active patient engagement in motor relearning. Importantly, robotic glove therapy demonstrates practical feasibility due to its wearable design, adaptability to various impairment levels, and potential for semi-supervised or home-based deployment. By increasing training intensity without proportionally increasing therapist workload, this innovation offers a scalable rehabilitation solution, particularly relevant for healthcare systems facing workforce limitations and growing stroke prevalence. While methodological heterogeneity and limited sample sizes constrain definitive conclusions, current evidence supports robotic glove therapy as a clinically promising and operationally feasible adjunct to conventional stroke rehabilitation, warranting larger standardized trials and contextual implementation studies in emerging healthcare settings.